Called to preach: fulfilling the high calling of expository preaching - Lawson, Steven J. (Baker Books, a division of Baker Publishing Group, 2022)
"With insights from Scripture and examples from church history, this practical guide offers aspiring preachers the tools they need to discern whether they are being called to expository preaching"--